2017
DOI: 10.1021/jacs.7b07422
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Dependent DNA Recognition and Cell Internalization of Designed, Basic Peptides

Abstract: A fragment of the DNA basic region (br) of the GCN4 bZIP transcription factor has been modified to include two His residues at designed i and i+4 positions of its N-terminus. The resulting monomeric peptide (brHis2) does not bind to its consensus target DNA site (5′-GTCAT-3′). However, addition of Pd(en)Cl2 (en, ethylenediamine) promotes a high-affinity interaction with exquisite selectivity for this sequence. The peptide–DNA complex is disassembled by addition of a slight excess of a palladium chelator, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…Before testing catalytic reactivities, we considered it fundamental to obtain more information on the internalization requirements of the miniprotein. Our previous studies had demonstrated that mixing the peptide brHis 2 with PdCl 2 (en) produces relatively stable peptide palladium complexes (detected by ESI‐MS), and that these metallopeptides go inside HeLa cells at concentrations as low as 5 μ m …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before testing catalytic reactivities, we considered it fundamental to obtain more information on the internalization requirements of the miniprotein. Our previous studies had demonstrated that mixing the peptide brHis 2 with PdCl 2 (en) produces relatively stable peptide palladium complexes (detected by ESI‐MS), and that these metallopeptides go inside HeLa cells at concentrations as low as 5 μ m …”
Section: Resultsmentioning
confidence: 99%
“…[11] Quite recently,w ed iscovered that introducing two histidine residues in the strategic ia nd i + 4p ositions of the basic region of aG CN4 bZIP transcription factor (brHis 2 ) [12] triggers its DNAb inding upon addition of PdCl 2 (en) (en = ethylenediamine,F igure 1). [13] Interestingly,t he palladium additive also sparks an efficient membrane translocation into mammalian cells.Specific control experiments confirmed that these properties result from stapling of the two histidines by the added metal.…”
Section: Introductionmentioning
confidence: 99%
“…[124] MascareÇas andc o-workersa lso demonstrated in 2020h ow small peptides such as brHis2 (Figure 49 B), consisting of the basic domains of bZIP transcription factorsm utated to include two histidine residues (at i and i + 4p ositions), react with palladium(II) sources to generate catalytically active, stapled palla-do-miniproteins. [125] Importantly,w hile the peptidep recursor brHis2 failed to translocate across cell membranes on its own, the stapled pallado-protein undergoes efficient cell internalization into living mammalian cells (mediated by integrin receptors), [126] where it performsp alladium-promotedd epropargylation reactions withoutc ellular fixation (Figure 49 B). The effectivenesso ft he approach is likely associated to as ynergistic beneficial effect of the conformational constrain introduced by the metal bridge, and ap rotective role of the peptides caffolding, whicha voids ar apid deactivation of the metal catalyst (Figure 49 C).…”
Section: Cleavage Of O-propargyland N-propargyloxycarbonyl (Poc)mentioning
confidence: 99%
“…Mascareñas and coworkers evaluated the intracellular reactions within mammalian cells by using Pd(II)-coordinated peptides [ 141 ]. These authors previously discovered that introducing two histidine residues in the i and i + 4 positions of the basic region of the GCN4 bZIP transcription factor 129 triggered an efficient membrane translocation into the mammalian cells upon addition of a Pd(II) source by stapling the peptide ( Figure 27 ) [ 142 ]. They first confirmed the importance of the stapled peptide on the cell internalization of Pd(II) using tetramethylrhodamine (TMR)-labeled 129 and the fluorescent 130 complex ( Figure 27 ).…”
Section: Drug Applicationsmentioning
confidence: 99%